Design and analysis for robotic arm position for automatic electric vehicle - Kharde, Mukund Ramdas; Kalam, Sayyad Abdul; Teku, Kalyani; Reddy, Thumu Srinivas; Satya Srinivas, Gollapalli Veera; Kollamudi, Pavani; Fariddin, Shaik Baba; Kumar, Gopinati Pranay (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Nowadays electric vehicles (EV) utilization is increasing. Because of charging issues, EVs are troubling people at the time of the journey because of the lack of charging stations. Therefore, to overcome these issues, robotic arm position for automatic electric vehicle is introduced in this analysis. This vehicle is operated through solar, so charging issues are overcome. The robotic arm position for automatic electric vehicle is fully automated by 4 infrared radiation (IR) sensors, which are placed in variations, back and other sides with particular speed limit variations, so that accidents can be avoided. The Flux in hand gloves can operate without manual operation while driver is sleeping. This analysis uses Raspberry Pi, python software with machine learning (ML) algorithm (support vector machine). Hence, this robotic arm position for automatic electric vehicle shows better results in terms of charging issues, accident ratio and driver presence.